Penyelamatan Manuskrip Pesantren di Kabupaten Sumenep Melalui Inventarisasi, Digitalisasi, Penghimpunan, dan Katalogisasi - Syafiqurrahman; Raziq, Luthfi; Syakur, Abd; Wardi, Moh. (TAAWUN, 2024)
Pesantren is one of the oldest Islamic educational institutions in Indonesia, which since its inception has participated in building the civilization of the people through movements and works produced by Pesantren in the form of pesantren manuscripts. The implementation of this service has the aim of saving and utilizing pesantren manuscripts for scientific development. The method and model of this service, namely Participatory Action Research (PAR). Thus, it is the right way to realize the expectations of the assistance described above. With PAR, the service process in saving this pesantren manuscript will run to completion. There are several steps taken in this service, namely conducting inventories, providing understanding to the community, digitizing manuscripts, collecting manuscripts, building networks of cooperation with the regional library of Sumenep, cataloging manuscripts, and packaging in the form of plastic folders. This service produces manuscripts in digital form. In conclusion, First, the manuscript profile is well described. Second, there are several strategies carried out by the service to save the manuscripts of pesantren in Sumenep, starting from digitization, cataloging, and packaging using plastic materials. Third, this Community Service contributes to saving the existence of pesantren manuscripts in Sumenep.